2012
DOI: 10.1007/s12603-011-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the literature concerning the relationship between obesity and mortality in the elderly

Abstract: Introduction Obesity is a risk factor for chronic diseases and premature mortality, but the extent of these associations among the elderly is under debate. The aim of this systematic literature review (SR) is to collate and critically assess the available information of the impact of obesity on mortality in the elderly. Methods In PubMed, there are three-hundred twelve papers on the relationship between obesity and mortality among older adults. These papers were analysed on the basis of their abstracts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 45 publications
8
60
2
8
Order By: Relevance
“…Within the context of cardiovascular diseases, several studies have shown a survival benefit in non-CKD elderly patients after intentional weight loss. 20 The present results are not in agreement with this in hemodialysis patients, but it did not distinguish between intentional and unintentional weight losses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Within the context of cardiovascular diseases, several studies have shown a survival benefit in non-CKD elderly patients after intentional weight loss. 20 The present results are not in agreement with this in hemodialysis patients, but it did not distinguish between intentional and unintentional weight losses.…”
Section: Discussioncontrasting
confidence: 99%
“…19 However, the majority of previous studies that evaluated the association between BMI and survival in general geriatric populations found a U-shaped relationship in which the lowest mortality rates corresponded to BMIs ranging between 23.5 and 27.5 kg/m 2 . 20 In the present study of European elderly hemodialysis patients, there were only 11.2% obese patients, which is 10% less than the proportion reported by Kalantar-Zadeh et al 21 in a nonelderly hemodialysis population in the United States.…”
Section: Discussioncontrasting
confidence: 58%
“…64 However, the results of one systematic review found an increased mortality in obese older adults. 103 Energy reserves during time of stress, illness and trauma, protection against osteoporosis, lower risk of falls, and reduced post-fall trauma, may explain some of the observed protective effect seen in studies of overweight and obesity with mortality in older adults. Results could also be complicated by disease burden, health and hydration status, as well as limitations with anthropometric measurements in this population.…”
Section: Body Weight and Compositionmentioning
confidence: 99%
“…Thus BMI depends not only on adiposity but also on the loss of muscle mass which has opposing effects on mortality (13) , so that BMI may not be a good indicator of obesity in the elderly. It is suggested that measures of adiposity such as waist circumference (WC) or the waist:hip ratio, which better reflect visceral fat, may be more useful at assessing obesity risk as they are better at predicting CVD and mortality in older subjects (22)(23)(24)(25)(26) . Central obesity has been defined as a WC > 102 cm for men and >88 cm for women, or a waist:hip ratio ⩾0·9 for men and ⩾0·85 for women (27) .…”
mentioning
confidence: 99%